2011
DOI: 10.1007/s12011-011-9229-0
|View full text |Cite
|
Sign up to set email alerts
|

Options for the Production of Selenized Chicken Meat

Abstract: A 42-day experiment was conducted to compare the effects of various levels of sodium selenite (SS) and Se-enriched yeast (SY) on chicken productivity, carcass traits, and breast Se concentration. Six hundred 1-day-old Cobb 500 broiler chicks were placed on 1 of 6 experimental treatments. The treatments consisted of feeding a diet without Se supplementation (basal diet) or basal diet with 0.6 mg/kg supplemented Se supplied by SS, SY, or a mix of the two (0.45 SS + 0.15 SY; 0.3 SS + 0.3 SY; 0.15 SS + 0.45 SY). C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 18 publications
3
16
0
Order By: Relevance
“…These outcomes consistently confirmed that the efficacy of Se from Seenriched yeast and HPSeKS was comparable, but higher than that of Se from sodium selenite when used tissue Se concentration as an indicator [19]. Numerous reports similarly observed broilers received Se from Se-enriched yeast or Seenriched alga had higher (p<0.05) tissue Se content than those received Se from sodium selenite [4,5,7,8,38,39]. On the other hand, Se from Se-enriched garlic, cabbage [10], and malt [40] did not improve Se concentrations in chick tissues, reflecting that selenomethionine is not the major Se species in these plants.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…These outcomes consistently confirmed that the efficacy of Se from Seenriched yeast and HPSeKS was comparable, but higher than that of Se from sodium selenite when used tissue Se concentration as an indicator [19]. Numerous reports similarly observed broilers received Se from Se-enriched yeast or Seenriched alga had higher (p<0.05) tissue Se content than those received Se from sodium selenite [4,5,7,8,38,39]. On the other hand, Se from Se-enriched garlic, cabbage [10], and malt [40] did not improve Se concentrations in chick tissues, reflecting that selenomethionine is not the major Se species in these plants.…”
Section: Discussionsupporting
confidence: 65%
“…Payne and Southern [26] found no effect of sources or levels of Se (0 to 0.3 mg/kg) on carcass traits in broilers. Several reports [5,7,34] also reported that carcass characteristics of broilers were not influenced by different sources and levels of Se (0 to 0.6 mg/kg). However, Upton et al [32] observed that some parameters of cutup yields of high-yielding broilers were increased with organic Se supplementation (0 to 0.2 mg/kg) from Se-enriched yeast.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This trace element is also involved in biochemical processes such as reproductive and immune functions, and the production of thyroid hormones (KOHRL et al, 2000). KRSTIÉ et al (2012), reported that the concentration of selenium in the soil in many parts of the globe is insuffi cient to ensure the minimal trace element in foods, causing its defi ciency in humans and consequently decrease the activity of several selenoenzymes necessary for physiological homeostasis of the organism. CROMWELL et al (1999) noted that the concentration of selenium in corn and soybean meal of 15 American states, ranged between 0.02 to 0.29mg kg -1 and 0.08 to 0.95mg kg -1…”
Section: Introductionmentioning
confidence: 99%
“…CLOSE (1998) and KRSTIÉ et al (2012) reported that selenium is currently added to the poultry feed at concentrations ranging from 0.15 to 0.5mg kg -1…”
Section: Introductionmentioning
confidence: 99%